(untitled) - Krizan, Frantisek; Gurnak, Daniel (Doprava a spoje, 2008)
The aim of the paper is to analyze selected problems of the urban mass transportation (UMT) in Bratislava town. Applied methodology was a perception analysis. The results shows respondents perceive worsen quality of traveling by UMT in comparison with the situation a few years ago. The average time passengers spend waiting at UMT stops is 15,6 min and the average time of traveling is 71,3 min.